The Cambridge handbook of hydrogen and the law / edited by Ruven Fleming. - Fleming, Ruven (Cambridge University Press, 2025)
The Cambridge Handbook of Hydrogen and the Law is the first comprehensive reference work on the regulation of this key area in the energy transition. It is global in scope, featuring chapters that explain the legal situation on hydrogen regulation in Europe, the USA, Latin America, Oceania, the Middle East / North Africa, and Southeast Asia. It includes chapters covering all relevant legal aspects of the hydrogen value chain from production to end use, making it the first in-depth work on the interplay of hydrogen and the law. Leading scholars and practitioners discuss the creation of hydrogen markets, the role of local authorities, sustainability and public participation in hydrogen regulation, the permitting regimes for electrolysers, offshore hydrogen, the regulation on hydrogen transportation and storage, indigenous perspectives on hydrogen, the regulation of hydrogen in heating and the regulation of electricity storage in the form of hydrogen. This title is also available as Open Access on Cambridge Core.